Analysis of the glow curve of KMgF3:Lu compounds without resorting to the quasi-equilibrium approximation - Marcazzo, Salvador Julian (2014)
In this article we report an expression for the thermoluminescence light, which is derived from the set of differential equations by assuming negligible retrapping, but without resorting to the quasi-equilibrium approximation. The expression has been employed for analysing the glow curve of KMgF3:Lu fluoroperovskite compounds.